Continuous-Flow Magnetic Separation with Permanent Magnets for Water Treatment - Borghi, Chiara Caterina <1986> (Alma Mater Studiorum - Università di Bologna, 2014)
More efficient water treatment technologies would decrease the water bodies’ pollution and the actual intake of water resource. The aim of this thesis is an in-depth analysis of the magnetic separation of pollutants from water by means of a continuous-flow magnetic filter subjected to a field gradient produced by permanent magnets. This technique has the potential to improve times and efficiencies of both urban wastewater treatment plants and drinking water treatment plants. It might also substitute industrial wastewater treatments. This technique combines a physico-chemical phase of adsorption and a magnetic phase of filtration, having the potential to bond magnetite with any conventional adsorbent powder. The removal of both Magnetic Activated Carbons (MACs) and zeolite-magnetite mix with the addition of a coagulant was investigated. Adsorption tests of different pollutants (surfactants, endocrine disruptors, Fe(III), Mn(II), Ca(II)) on these adsorbents were also performed achieving good results. The numerical results concerning the adsorbent removals well reproduced the experimental ones obtained from two different experimental setups. In real situations the treatable flow rates are up to 90 m3/h (2000 m3/d).